CULTURAL AND LINGUISTIC CHALLENGES IN GLOBAL MARITIME EDUCATION (NAVIGATING ENGLISH USAGE) - Irma Rasita Gloria Barus; Ronald Simanjuntak; Rosna Yuherlina Siahaan; Gigih Prastyan Toko; Ira Resmayasari (Meteor STIP Marunda, 2024)
This qualitative study investigates cultural and linguistic challenges faced by 45 junior cadets in global maritime education, focusing on English usage. Through interviews and focus group discussions, diverse English proficiency levels were identified among participants, highlighting the need for tailored language training programs. Communication challenges, particularly in understanding technical terminology and navigating cultural differences, emphasize the importance of targeted language instruction and cross-cultural training initiatives. Aligning with the International Maritime Organization's Standards of Training, Certification, and Watchkeeping (STCW), the study emphasizes the significance of linguistic competence and cultural awareness in ensuring safety and efficiency within maritime crews. The findings emphasize the importance of integrating language training initiatives into maritime education curriculum and fostering a culture of inclusivity and professionalism within the maritime industry.